Male Gender and Arterial Hypertension are Plaque Predictors at Coronary Computed Tomography Angiography - Oliveira,Joselina Luzia Menezes (2015)
Background: Systemic Arterial Hypertension (SAH) is one of the main risk factors for Coronary Artery Disease (CAD), in addition to male gender. Differences in coronary artery lesions between hypertensive and normotensive individuals of both genders at the Coronary Computed Tomography Angiography (CCTA) have not been clearly determined. Objective: To Investigate the calcium score (CS), CAD extent and characteristics of coronary plaques at CCTA in men and women with and without SAH. Methods: Prospective cross-sectional study of 509 patients undergoing CCTA for CAD diagnosis and risk stratification, from November 2011 to December 2012, at Instituto de Cardiologia Dante Pazzanese. Individuals were stratified according to gender and subdivided according to the presence (HT +) or absence (HT-) of SAH. Results: HT+ women were older (62.3 ± 10.2 vs 57.8 ± 12.8, p = 0.01). As for the assessment of CAD extent, the HT+ individuals of both genders had significant CAD, although multivessel disease is more frequent in HT + men. The regression analysis for significant CAD showed that age and male gender were the determinant factors of multivessel disease and CS ≥ 100. Plaque type analysis showed that SAH was a predictive risk factor for partially calcified plaques (OR = 3.9). Conclusion: Hypertensive men had multivessel disease more often than women. Male gender was a determinant factor of significant CAD, multivessel disease, CS ≥ 100 and calcified and partially calcified plaques, whereas SAH was predictive of partially calcified plaques.